1996
DOI: 10.1093/infdis/174.3.537
|View full text |Cite
|
Sign up to set email alerts
|

Immunoprophylaxis against Klebsiella and Pseudomonas aeruginosa Infections

Abstract: To determine if passive immunization could decrease the incidence or severity of Klebsiella and Pseudomonas aeruginosa infections, patients admitted to intensive care units of 16 Department of Veterans Affairs and Department of Defense hospitals were randomized to receive either 100 mg/kg intravenous hyperimmune globulin (IVIG), derived from donors immunized with a 24-valent Klebsiella capsular polysaccharide plus an 8-valent P. aeruginosa O-polysaccharide-toxin A conjugate vaccine, or an albumin placebo. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 21 publications
0
56
1
1
Order By: Relevance
“…The anti-CPS vaccine approached worked well to protect rodents from death in experimental models of severe K. pneumoniae infection (39,40). The vaccine was evaluated for safety in humans (35), and the use of CPS-specific hyperimmune IVIG decreased the incidence and severity of Klebsiella infections in a human clinical trial (41). Previous work also demonstrated that vaccines (either monovalent or polyvalent) can protect against multiple (as many as 71) Klebsiella capsule types (35,42).…”
Section: Resultsmentioning
confidence: 99%
“…The anti-CPS vaccine approached worked well to protect rodents from death in experimental models of severe K. pneumoniae infection (39,40). The vaccine was evaluated for safety in humans (35), and the use of CPS-specific hyperimmune IVIG decreased the incidence and severity of Klebsiella infections in a human clinical trial (41). Previous work also demonstrated that vaccines (either monovalent or polyvalent) can protect against multiple (as many as 71) Klebsiella capsule types (35,42).…”
Section: Resultsmentioning
confidence: 99%
“…Efficacy against burn wound infection using immune globulin from patients immunized with a cellular extract of P. aeruginosa showed protective efficacy in the early 1980s (43,44) but this product was not further pursued. A hyperimmune IVIg product prepared from plasma donors immunized with an octavalent P. aeruginosa LPS O-side chain conjugate vaccine (45,46) showed no protective efficacy in patients in intensive care units (47). This may have been due to low Ab coverage for a sufficient diversity of serologically distinct O-Ags, or possibly to an overall low infection rate precluding an adequate sample size for documentation of the IVIg efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…This same group is developing passive reagents (19); however, a clinical trial using i.v. hyperimmune globulin elicited with this same vaccine was stopped because of adverse effects and no evidence of efficacy (20). In mouse experiments, either intramuscular or IN administration of monovalent O antigen conjugates that were included in the octovalent vaccine was found to elicit an IgG response in the lung but only in the presence of adjuvant; only the IN immunization with adjuvant elicited an IgA response at that site.…”
Section: Discussionmentioning
confidence: 99%